Phytoplankton Composition in The Koto Panjang Dam, Kampar Regency Riau - Rina Maria; Asmika H Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe increment of the number of floating cages in the Koto Panjang Dam may result on increment of organic materials in the water and thus affect the presence of phytoplankton. A study aims to understand the phytoplankton composition around the cages area was conducted on April-May 2018. Samplings were conducted 3 times, once/week. There were 3 stations namely Station 1 area with 100-150 floating cages, Station 2 area with 200-300 floating cages and Station 3 area with 946 floating cages. In each station, there were 3 sampling points, in the surface, in 2 Secchi depth, and in 4 Secchi depth. Water quality parameters measured were transparency, temperature, pH, dissolved oxygen, free carbon dioxide, nitrate and phosphate. Results shown that there were 8 genera presents, namely Chlorophyceae (29 species), Zygnematophyceae (17 species), Trebuoxiophyceae (2 species), Cyanophyceae (14 species), Bacillariophyceae (14 species), Meidiophyceae (1 species), Cryptophyceae (1 species) and Euglenophyceae (1 species). They were consisted of 79 phytoplankton species. As the number of cages increase, types of phytoplankton present decrease. However, there is relationship between cages and abundance. As the number of cages increase, phytoplankton abundance also increase. The highest abundance was 72,468 cells/L (Station 3) and the lowest was 24,580 cells/L (Station 1). Other water quality parameter measured were transparency : 101-138 cm; temperature : 28.3-31.70C; pH : 5.0-5.5; dissolved oxygen : 2.21-7.23 mg/L; free carbon dioxide : 11.09-26.93 mg/L; nitrate : 0.06-0.17 mg/L and phosphate : 0.07-0.26 mg/L. Based on data obtained, it can be concluded trophic state of Koto Panjang reservoir was categorized as eutrophic. Keyword: Koto Panjang Reservoir, Water quality, Organic Matter, Eutrophic